1959
DOI: 10.1136/bmj.1.5119.401
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline-secreting Neuroblastomata

Abstract: of sodium and aldosterone possessed by amphenone. Thyroid function also was not affected. SU 4885 is much the less toxic of the two drugs, gastric disturbances being the only consistent symptom. The excessive drowsiness which severely limits the use of amphenone did not occur.Although the action of SU 4885 on other adrenal steroids, notably oestrogens, has not yet been studied, the relatively large doses required to suppress hydrocortisone together with the formation of 1 l-deoxyhydrocortisone and probably deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1960
1960
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Increased urinary excretion of catecholamines or their metabolites, or both, has been reported recently in association with ganglioneuroma, ganglioneuroblastoma and neuroblastoma (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These neoplasms are embryologically related, having a common origin from neural-crest ectoderm.…”
Section: Discussionmentioning
confidence: 94%
“…Increased urinary excretion of catecholamines or their metabolites, or both, has been reported recently in association with ganglioneuroma, ganglioneuroblastoma and neuroblastoma (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These neoplasms are embryologically related, having a common origin from neural-crest ectoderm.…”
Section: Discussionmentioning
confidence: 94%
“…In addition they stated that in the case of Mason et al (1957) the portion of the tumour used to confirm the presence of pressor amines might possibly have been the portion containing phaeochromocytes. Describing three patients with noradrenaline secreting neuroblastomas, Isaacs, Medalie and Politzer (1959) concluded that neuroblasts themselves were responsible for the secretion of catecholamines or for the hyperstimulation of normal chromaffin tissue, and that if the former was acceptable it implied that chromaffin tissue was not essential for the production of catecholamines. The potential complexity of the cell content of any tumour originating from the primitive neural crest must inevitably make classification difficult, although it is easy to understand how more than one element can be represented.…”
Section: Discussionmentioning
confidence: 99%
“…It appears, then, that the tumor was unable to metabolize the norepinephrine formed within it, at least by the important and perhaps primary mechanism of 0-methylation (23). DISCUSSION Increased amounts of norepinephrine and epinephrine excretion have been found in cases of neuroblastoma by Isaacs, Medalie and Politzer (28) and Mason and associates (29). The presence of pressor amines in the tissue of a neuroblastoma was reported recently by Graham (30).…”
mentioning
confidence: 80%